2021
DOI: 10.1002/hed.26665
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 on head and neck cancer diagnosis and disease extent

Abstract: Background Due to COVID‐19, diagnostic delays and a surge of advanced head and neck cancer (HNC) is anticipated. We hereby evaluate patient and tumor characteristics before and during the early COVID‐19 period. Methods Retrospective review of patients with HNC presented at a multidisciplinary tumor conference from May 14, 2020 to June 18, 2020 was performed and compared to a similar 6‐week period a year before. Demographics, time to diagnosis, and tumor characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
81
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(102 citation statements)
references
References 29 publications
13
81
7
1
Order By: Relevance
“…Consistent with previous reports [3] , overall number of patient encounters decreased during the initial stages of the pandemic. Contrary to what has been previously reported [7] , we report stability in number of patients presenting with new head and neck malignancies. The proportional increase in patients with malignant diseases, decrease in benign patient visits, and decrease in time from referral to initial clinic visit for mucosal SCC patients suggests that there were more available head and neck surgical oncology clinic appointments, likely due to less patients with benign pathology seeking medical care during the early months of the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Consistent with previous reports [3] , overall number of patient encounters decreased during the initial stages of the pandemic. Contrary to what has been previously reported [7] , we report stability in number of patients presenting with new head and neck malignancies. The proportional increase in patients with malignant diseases, decrease in benign patient visits, and decrease in time from referral to initial clinic visit for mucosal SCC patients suggests that there were more available head and neck surgical oncology clinic appointments, likely due to less patients with benign pathology seeking medical care during the early months of the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite more advanced clinical nodal staging for our cohort, T staging was not significantly more advanced during the pandemic. This is in contrast to a prior study by Kiong et al which used similar methods over only a six-week period during the pandemic and found that in a smaller cohort, mucosal SCC patient's median primary tumor size was greater and T stage was more advanced during the pandemic [7] . It is important to note that our cohort consists of a higher proportion of oral cavity and larynx subsite patients compared to the paper by Kiong et al of which nearly half the mucosal SCC patients were oropharynx.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Access to both primary medical and dental services is currently limited and patients with head and neck cancer will be missing lifesaving opportunities for detection. One US study in May 2020 reported a 25% reduction in newly diagnosed head and neck malignancy and the median primary tumour size was statistically significantly larger 5. Similar evidence was observed in Turin, Italy, during their March 2020 lockdown when they received significantly fewer urgent referrals and diagnosed only 12% of predicted head and neck oncology caseload 6…”
mentioning
confidence: 79%
“…In developed countries, the use of inpatient care and subsequent hospitalization de cit in oncology was estimated to be 7%-35% [19][20][21][22]. All oncological subspecialties in the US experienced signi cant decreases in new patient visits and surgery capacity during COVID-19 [23], with a 25% reduction in newly diagnosed head and neck malignancies [24].…”
Section: Discussionmentioning
confidence: 99%